EVALUASI PROGRAM AL-MIFTAH LIL ULUM DI PPTQ AL-MANNAN TULUNGAGUNG: PENDEKATAN MODEL CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) - Adhiswar Azizi; Ishthifaul Ashfia; Ni'matul Ula; Ayu Anis Eliyana Azis; Ahmad Yanto Ferdiansyah (Pascasarjana Universitas Al-Qolam Malang, 2026)
This study aims to evaluate the Al-Miftah lil Ulum program at PPTQ Al-Mannan Tulungagung using the CIPP (Context, Input, Process, Product) evaluation model. The Al-Miftah lil Ulum method, developed by Pondok Pesantren Sidogiri, has been widely adopted by various Islamic educational institutions as an innovative approach to learning classical Islamic texts (kitab kuning). A qualitative approach with a single case study design was employed in this research. Data were collected through participatory observation over three meetings, semi-structured interviews with 15 purposively selected informants consisting of the pesantren leader, program coordinator, teachers, students, and administrators, as well as documentation studies of archives and activity photographs. The Miles and Huberman interactive model was used for data analysis, encompassing data reduction, data presentation, and conclusion drawing. The findings reveal that from the context aspect, this program is highly suitable for the needs of beginner students who mostly have not yet learned nahwu (Arabic grammar). From the input aspect, the program has certified teachers and complete teaching materials, though still constrained by limited learning facilities. From the process aspect, learning proceeds according to the six-stage standard procedure, albeit sometimes hindered by teachers' busy schedules. From the product aspect, the program achieved a 100% pass rate in the first volume with an average score of 82. This study concludes that the Al-Miftah lil Ulum program is effective for beginner students, while recommending improvements in infrastructure and scheduling. The CIPP model is suggested for adoption by other pesantren in evaluating their learning programs.